A Comparative Statistical Study on Social Media Usage and Its Impact on the Mental Well-Being of Young Employees - Ahmad, Sajjad; Smerat, Aseel; Wong, Dr Wing-Keung; Bilal, Dr Muhammad (Sigmae, 2025)
This research study aims to statistically analyze the impact of social media usage on the mental well-being of employees. Social media plays a significant role in everyday life, impacting social, professional, and personal aspects. Despite many advantages, excessive use of social media may harm users’ mental health. The study’s objective is to investigate how employees’ mental health, job satisfaction, stress levels, anxiety, and overall productivity are influenced by their use of social media in both public and private sector organizations. In this regard, the data of 410 respondents showed an age range of 21 to 31 years old (M = 26.25). For this research study, employees / skilled personnel/schoolteachers (Public and Private), banking sector personnel, hotel staff, and courier services organizations in Pakistan were nominated to collect the samples. The age group of employees was the focal point of the study, as most young workers are interested in using social media. Correlation, regression, NOVA, and coefficient analysis reveal a strong relationship between social media and the mental well-being of employees, which leads to testing of Hypotheses H1 to H3. Resultantly, the Beta value β = 0.220 (p < .001), F-statistic = 20.672, and t-value of 4.547 were found statistically significant. The positive angles incorporate enhanced social connections, self-expression, and access to support organizations. Comparatively, the adverse results, for example, cyberbullying, social correlation, rest unsettling influences, and feelings of dread toward missing an opportunity, are likewise investigated.